The Effect of Return On Asset, Current Ratio, and Debt to Equity Ratio on Profit Growth in Cosmetic and Household Goods Companies Listed on The Indonesia Stock Exchange in The Period 2019-2023 - Desshyfa, Rizana Tarissa; Saputra, Fendi (CV. Lenggogeni Data Publishing, 2025)
This study aims to examine the impact of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on profit growth in cosmetic and household goods companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. These companies play a pivotal role in the primary consumer goods sector, characterized by steady demand despite economic fluctuations. Utilizing a quantitative approach, this research analyzes secondary data from annual financial statements of selected companies. Data were processed using EViews 12 software and the Fixed Effects Model was employed for analysis. The findings reveal that ROA positively and significantly influences profit growth, while CR and DER show no significant effect. These results underscore the importance of asset utilization in driving profitability and provide strategic insights for corporate management and investors. By shedding light on key financial indicators, this study contributes to a deeper understanding of profit determinants in the consumer goods sector.